2019
DOI: 10.1021/acs.est.9b00538
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Effect of Metal Ions on Photogeneration of Reactive Species from Dissolved Organic Matter

Abstract: The photogeneration of reactive species (RS) from dissolved organic matter (DOM) exhibits a great impact on the attenuation of pollutants in natural waters. However, the effect of metal ions on the photogeneration of excited triplet-state DOM (3DOM*), singlet oxygen (1O2), and hydroxyl radical (•OH) by effluent organic matter (EfOM), fulvic acid (FA), and humic acid (HA) is poorly understood. Here, we provided the first evidence that the quenching of 3DOM* was positively correlated with the complexation capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 59 publications
(146 reference statements)
3
62
0
Order By: Relevance
“…This analysis does not make assumptions about a linear relationship between the fluorescence intensity change and the metalbound ligand concentration; rather, it estimates the contribution of unquenched fluorescence. 75,76 Although there are many different modifications of the Stern-Volmer analysis, 55,76 the modification The ability of metal ions, particularly Cu 2+ and Fe 3+ , to complex with NOM and the resulting complexation parameters have been reported previously, 18,21,24,28,33,35,45,48,67,68,[77][78][79][80][81][82][83] and qualitatively, our results fit reasonably well within the range of values reported for each metal ion. Supplementary Table S3 reports a range of logK ML values at similar pHs.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This analysis does not make assumptions about a linear relationship between the fluorescence intensity change and the metalbound ligand concentration; rather, it estimates the contribution of unquenched fluorescence. 75,76 Although there are many different modifications of the Stern-Volmer analysis, 55,76 the modification The ability of metal ions, particularly Cu 2+ and Fe 3+ , to complex with NOM and the resulting complexation parameters have been reported previously, 18,21,24,28,33,35,45,48,67,68,[77][78][79][80][81][82][83] and qualitatively, our results fit reasonably well within the range of values reported for each metal ion. Supplementary Table S3 reports a range of logK ML values at similar pHs.…”
Section: Discussionsupporting
confidence: 88%
“…Further studies using complimentary techniques are needed to validate these findings, given the limitations of this study. It has been shown previously that NOM reactivity, via the formation of singlet oxygen, decreases in the presence of metals, 56,68,92 so the results of this study show that this decrease is not due to conformational changes affecting the ability of ground state oxygen to quench the excited triplet. We also showed that the analysis performed in this study, although very simplified, is applicable to both fluorescence quenching and enhancement interactions.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Metal ions tend to bind to NOM, mainly through the phenolic and carboxylic functional groups [6]. The binding of metal ions to NOM not only altered the bioavailability of metal ions, but also affected the photophysical and photochemical properties of NOM [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, autochthonous aquatic DOM includes extracellular polymeric substances (EPS), autochthonous humic-like substances (AHLS), protein-like substances (PLS), aromatic amino acids of various nature, etc (Shammi et al 2017a(Shammi et al , 2017b(Shammi et al , 2017cGuidi et al, 2016;Zhang et al, 2009;Mostofa et al 2013;Yamashita and Tanoue, 2003). These substances occur as major fractions, even if very diluted, in surface waters of lakes, estuaries and oceans 7 , thus they control many important biogeochemical functions and processes in aquatic systems, including cycling of C (Zark and Dittmar, 2018;Guidi et al, 2016;Amon and Benner, 1994), N (Yue et al, 2018;Liang et al 2019), P (Guidi et al, 2016;Carpenter et al, 1998;Parsons et al, 2017) and trace elements (Wan et al, 2019;Helms et al, 2013), as well as nutrient changes associated with diurnal sunlight-induced planktonic photosynthesis (Gao et al, 2010;Jung et al, 2013;Segschneider and Bendtsen., 2013).…”
Section: Introductionmentioning
confidence: 99%